Pediatric open-globe injury: Current perspectives, surgical principles, and literature review - Jovi C. Y. Wong; Yoshihiro Yonekawa (Taiwan Journal of Ophthalmology, 2025)
Open-globe injury (OGI), referring to the full-thickness violation of the eye wall, is a severe consequence of ocular trauma which can lead to permanent vision loss. Here, we review the current literature on pediatric OGI including a focused review of studies published in the past 10 years. Scoring systems for final visual prognosis, important aspects of clinical examination, and imaging at the point of care are discussed. We furthermore provide an overview of primary and secondary surgical management of the initial OGI and sequelae. Amblyopia management differentiates pediatric from adult visual rehabilitation following OGI, and we discuss the current state-of-the-art approaches for the prevention of vision loss.